2011
DOI: 10.3892/ijo.2011.1187
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with the Chk1 inhibitor G�6976 enhances cisplatin cytotoxicity in SCLC cells

Abstract: Abstract. Acquired chemoresistance is a major obstacle in successful treatment of small cell lung cancer (SCLC). DNA damage responses can potentially contribute to resistance by halting the cell cycle following exposure to therapeutic agents, thereby facilitating repair of drug-induced lesions and protecting tumour cells from death. The Chk1 protein kinase is a key regulator in this response. We analysed the status of cell cycle checkpoint proteins and the effects of the Chk1 inhibitor Gö6976 on cisplatin toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…Although a prior study showed that CHK1 targeting could enhance the cytotoxicity of cisplatin in a small number of SCLC cell lines (40), the current study significantly expands upon this work and reports additional novel findings. First, by leveraging a large panel of molecularly profiled cell lines, we identify for the first time biomarker-defined SCLC subsets with enhanced vulnerability to CHK1 inhibition.…”
Section: Discussionmentioning
confidence: 70%
“…Although a prior study showed that CHK1 targeting could enhance the cytotoxicity of cisplatin in a small number of SCLC cell lines (40), the current study significantly expands upon this work and reports additional novel findings. First, by leveraging a large panel of molecularly profiled cell lines, we identify for the first time biomarker-defined SCLC subsets with enhanced vulnerability to CHK1 inhibition.…”
Section: Discussionmentioning
confidence: 70%
“…With this information we could then test the prediction that the inhibition of Chk1 would cause more cells to enter mitosis with damaged DNA and therefore generate additional micronuclei. 31 We observed that the percentage of micronuclei in cells co-treated with a checkpoint inhibitor and cisplatin was higher than the percentage of cells with micronuclei after treatment with cisplatin alone. This finding suggested that inhibiting Chk1 permits entry into mitosis, 32 which generates additional micronuclei.…”
Section: M059k Cells Treated With Cisplatin Undergo Checkpoint Adaptamentioning
confidence: 72%
“…It has also been shown that CHK1 inhibitors sensitize pancreatic cancer cells to gemcitabine or radiation [32] and that the sensitization mechanism is attributable to G2 checkpoint abrogation and inhibition of homologous recombination repair DNA damage response [14,16]. CHK1 inhibitors have been combined with numerous chemotherapeutics, including cisplatin [33,34] and paclitaxel [35]. Although we did not observe any sensitization when we combined AZD7762 with cisplatin (data not shown), we did see a reduction in both proliferation and clonogenic survival with both gemcitabine and pemetrexed, with a greater reduction in high versus low CHK1 expressing NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%